Effekter av skendräktighet och kastration på tikens beteende - Gåveby Sjöö, Natalie (2015)
Pseudopregnancy is a condition that is estimated to affect 40 % of all female dogs. Common symptoms are decreased activity level, weight gain, mammary enlargement, milk production, nesting behavior, anorexia and maternal behavior. The symptoms are displayed during metoestrus. Prolactin is one of the causes behind pseudopregnancy, but the full process is not yet known. Due to the fact that the condition affects that many bitches and often is recurrent, it is relevant to examine how the condition affects the bitch’s behavior and performance. The only permanent solution to the condition is castration, which is a surgical procedure that should be carefully considered before it is performed. The various risks related to the procedure, as well as how it may affect the behavioral and physiological state of the bitch, should be taken into consideration. Some of the side effects of castration are overweight, indiscriminate appetite, possible immunosuppression, delayed closing of the growth zones in the long bones and incontinence. Research has not yet found, besides a lower risk of developing mammary cancer, any beneficial effects of castration other than it eliminates the occurrence of pseudopregnancy. Research regarding the behavioral effects of castration has showed various results, but studies have reported that dominance behavior directed at family members increases as well as an increased reactivity, increased aggression behaviors, and the fact that the bitches are less bold and show more fear related behaviors.